A Study on the Planning and Targeting Applications in Forest Products Industry Enterprises (Case of Istanbul Province) - AKYÜZ, İlker; AKYÜZ, Kadri Cemil; ERSEN, Nadir; BAYRAM, Bahadır Çağrı; YILDIRIM, İbrahim (Journal of Anatolian Environmental and Animal Sciences, 2019)
Planning and targeting is the first step in the management function in enterprise. The success of management activities in every enterprise goes through effective planning and targeting. Top executives in an enterprise can have more time for planning and targeting than other functions. The junior administrative officer can have more time for other management functions. Priorities should be defined when determining processes in an enterprise. The first step in planning and targeting is to determine where you want to be reached. Also, the procurement and selection of all kinds of sources that will achieve these targets are included in planning and targeting. In this study, it was tried to determine how much the managers in the management stages of different forest industry enterprises operating in İstanbul had an important role in achieving the success of the enterprise in terms of planning and targeting function. In the study, a scale consisting of 31 expressions was set up for the planning and targeting to the employees in the enterprises. The number of surveys evaluated was 271. The results obtained from managers and other employees in different forest products sectors have been tested in SPSS statistical program with some other factors and the results are presented in detail.
Keywords: Planning; targeting; forest product industry; 15. Life on land